Bronchoconstriction-triggered cough in atopic cough: A retrospective study. (27th May 2016) - Ohkura, Noriyuki; Hara, Johsuke; Sakai, Tamami; Okazaki, Akihito; Abo, Miki; Kasahara, Kazuo; Fujimura, Masaki
ABSTRACT: Background: Atopic cough (AC) and cough variant asthma (CVA) were identified as major causes of chronic non-productive cough in a Japanese study. A characteristic feature of CVA is the presence of a heightened cough response to bronchoconstriction. On the other hand, the cough response to bronchoconstriction in AC remains unclear.Methods: Methacholine (Mch)-induced cough in AC was measured and compared with that in CVA. Diagnoses of AC and CVA were made based on patient history, physical examination, response to bronchodilator therapy, cough reflex sensitivity to capsaicin, spirometry, and airway responsiveness to methacholine.Results: Thirteen AC patients and 12 CVA patients in whom the criteria were met were recruited to the study. After inhalation of Mch at PC35-PEF40 that means milder bronchoconstriction than PC20-FEV1, cough was triggered a few times in AC. [cough number: 1/ 32 min (0–40)]. Conversely, significantly greater number of coughs was provoked in CVA, compared with AC [cough number: 35.5/ 32 min (25-125), p < 0.05].Conclusions: The cough response to bronchoconstriction is reduced in AC compared to CVA. This feature may be useful in the diagnosis of chronic cough.